Energizing Local Values For Tourism Services Improvement - Budi Purnomo (Register Journal, 2012)
People in most cultures would probably agree that politeness is needed during their interaction. However there may be differing opinions as to when they should be polite. In tourism industry, tourism service providers’ act as hosts and tourists act as guests. Typically hosts will try to act politely and use appropriate politeness norms when serving guests to ensure their satisfaction. The research findings show that the tourism service providers in Central Java use various unggah-ungguh ‘politeness norms’ when serving English speaking tourists and Indonesian speaking tourists. Besides that, there are some violations made by the tourism service providers in using unggah-ungguh ‘politeness norms’. The research findings also show that there are similar and different perspectives on unggah-ungguh ‘politeness norms’ between English speaking tourists with Western culture backgrounds and Indonesian speaking tourists with Indonesian culture backgrounds towards the politeness norms used by the tourism service providers in Central Java. The findings imply the needs of energizing unggah-ungguh ‘politeness norms’ which is discovered from well known noble Javanese values used by the tourism service providers for tourism service improvement.Keywords:  Local Values ; Politeness Norms;  Tourism Service Improvement